Masses, fat loads and estimated flight ranges of Skylarks Alauda arvensis captured during autumn migration in southern Italy. Issue 2 (3rd July 2017) - Scebba, Sergio; Sorrenti, Michele; Oliveri Del Castillo, Maria
ABSTRACT: From 1998 to 2015, 22 490 fully grown Skylarks were captured and ringed, using mist nets, from October to mid November, along the southern Tyrrhenian coast of Italy. We estimated fat loads and theoretical flight ranges for individual birds, using recorded body mass and visible fat score. The size-specific fat-free body mass, as the body mass of birds with no visible subcutaneous fat deposits, was estimated for all categories of wing length, verifying any differences between males and females identified using wing length; body mass (to 0.1 g) and visible fat score (values 0–6) were recorded in the field. Males were significantly heavier than females and more often had high scores of visible fat. Only a few birds had high fat scores (classes 5 and 6) and the proportion of individuals with no visible fat (class 0) was very low: most birds of both sexes fell into classes 3 or 4. Fat scores were positively correlated with the corresponding average body mass. The predicted flight range indicated that 70% of Skylarks captured would be unable to fly farther than 800 km: they would be able to reach their wintering grounds, spend the winter in Italy or reach the North African coast after a refuelling stop.